Predicting Early Death in Head and Neck Cancer—A Pilot Study - Talani, Charbel; Olsson, Hans; Roberg, Karin; Wiechec, Emilia; Almangush, Alhadi; Makitie, Antti A.; Farnebo, Lovisa (MDPI AG, 2025)
Background: The aim of this study was to evaluate biomarkers and biological characteristics of tumor biopsies from patients with head and neck cancer (HNC) to assess the risk of early death. Furthermore, we analyzed whether any combination of markers could be used for the prognostication of death within six months after cancer diagnosis.
Materials and Methods: Patients diagnosed with HNC, receiving curative treatment decision at a multidisciplinary tumor board meeting, and who died within six months of diagnosis were included in this study. Nine patients who died within six months from diagnosis were identified and matched according to the tumor site and stage to seventeen patients who survived for at least two years.
Results: The expression of markers was compared between the early-death patients and survivors. There was significantly higher Ki-67 expression in patients who died within six months than in those surviving for two years, with a mean difference of 21% (p = 0.038). A significant difference in cytoplasmic survivin expression was noted where early-death patients had increased expression compared to the survivors (p = 0.021). Furthermore, the intensity of survivin staining differed between the groups (p = 0.006).
Conclusions: The results of this pilot study indicate that Ki67 and survivin could be potential prognostic biomarkers for early death in patients with HNC and possibly included in a panel of prognostic markers of value for treatment decision making.